2021
DOI: 10.18203/2320-6012.ijrms20211340
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of severity and prognosis of acute pancreatitis through APACHE II and HAPS predictor models

Abstract: Background: Acute pancreatitis is one of the leading causes of hospitalization amongst all gastrointestinal disorders with high burden of morbidity and mortality. Predicting the progression of AP in terms of course and outcome to determine suitable management strategy and level of care is challenging. A number of predictor models are developed to predict the severity of acute pancreatitis but they vary in their definitions of severity. HAPS have been proposed as a simple scoring tool for assessment of severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It can reflect the overall physiological changes of the body and has good sensitivity and specificity. The previous study has shown that the APACHE-II score is closely related to the prognosis of SAP patients and is positively correlated with mortality [ 16 ]. In addition, the APACHE-II score is also associated with inflammation indicators such as CRP and the grade of peripancreatic effusion secondary to SAP [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can reflect the overall physiological changes of the body and has good sensitivity and specificity. The previous study has shown that the APACHE-II score is closely related to the prognosis of SAP patients and is positively correlated with mortality [ 16 ]. In addition, the APACHE-II score is also associated with inflammation indicators such as CRP and the grade of peripancreatic effusion secondary to SAP [ 17 ].…”
Section: Discussionmentioning
confidence: 99%